Are Women Financially Educated? A Study with Reference to Earning Women of Aurangabad District, Maharashtra - Bhonde-Saraf, Aparna (Indian Journal of Finance, 2016)
The global economic crisis has been a learning experience the world over. The causes of this crisis have been critically analyzed by many. One of the important reasons identified by the analysts is the complexity of financial instruments and the lack of proper understanding of them among the common investors. This clearly points out the inadequacy of financial education among the populace. Research from around the world reports inadequate financial literacy which raises serious concerns about the ability of individuals to secure their financial well-being. There is evidence that individuals under-save, fail to invest wisely, and are often indebted. The fact needs be emphasized that in today's world that promotes gender equality, both women and men need to be sufficiently financially literate. However, women often are observed to be playing a passive role in case of financial decision making. This research paper attempted to study the extent of financial awareness and financial knowledge among earning women. The paper concluded with an emphasis on financially educated women for financial well being.